Kajian Peningkatan Pati Resisten yang Terkandung dalam Bahan Pangan Sebagai Sumber Prebiotik - Raden Haryo Bimo Setiarto; Betty Sri Laksmi Jenie; Didah Nur Faridah; Iwan Saskiawan (Jurnal Ilmu Pertanian Indonesia, 2015)
Prebiotics are food ingredients that selectively stimulate the growth of probiotic bacteria in the colon. Resistant starch (RS) is the starch that can not be digested by digestive enzymes and resistant to gastric acid so it can reach the colon to be fermented by probiotic bacteria. There are treatments to increase the content of RS such as: autoclaving-cooling cycling, combination of lintnerized with autoclaving-cooling, and combination of debranching pullulanase with autoclaving-cooling. The results of techno-economical study showed that the combination of fermentation followed by autoclaving-cooling can be used as an alternative technique to increase the content of resistant starch in food more effectively and efficiently.